Calidad de vida en pacientes con Parkinson y relación con el nivel de sobrecarga en cuidadores que acuden al Centro Neurológico Sánchez - Gaona Chamba, Diego Fernando (2021)
Parkinson's disease affects both the individual and the family group because it involves physical, psychological, economic and social disorders that must be assumed by the caregiver, which requires constant adaptation. Both spouses and family members serve as caregivers, who may suffer emotional and physical stress, which may correspond to a greater disability of the patient. The present research had a quantitative, exploratory, cross-sectional and correlational approach with the objective of determining the quality of life in patients with Parkinson's disease and the overload generated in their caregivers who come to the Centro Neurológico Sánchez. The results obtained were: a regular quality of life level determined by obtaining an average score according to the PDQ39 quality of life questionnaire, with a higher prevalence in the male sex with 73.2% (n =30), compared to the female sex with 26.8 (n =11), whose age group is between 66-75 years old with 36.5% (n =15). In the group of caregivers, 48.7% (n = 20) presented a score lower than 55 showing a mild to intense overload, while 51.2% (n = 21) of these presented a score higher than 55 showing a level of intense overload, with the female sex predominating in the role of caregiver with 56.1% (n = 23). Pearson's correlation obtained a relationship coefficient between these two groups studied of .314, and a p-value of 0.46, concluding that there is a moderate direct relationship, the worse the quality of life, the greater the caregiver's overload. Key Words: Parkinson's Disease, Chronic Diseases, Family Caregivers, Health-Related Quality of Life, Black Substance